The impacts of dry stirred milling application on quality and production rate of the cement grinding circuits. (15th August 2020) - Altun, Okay; Benzer, Hakan; Karahan, Erdem; Zencirci, Sarp; Toprak, Alper
Graphical abstract: Highlights: The possible applications of dry stirred mill were discussed on a real-plant data. Dry stirred mill improves the energy efficiency of the overall circuit. Fine grinding improved quality and energy figures. Cement grinding flow sheets were proposed. Abstract: Cement industry has been one of the key processes within the modern life and attracted the interests of the researchers, machine manufacturers who are looking for the technological advances. As the industry itself is energy intense and contributes to CO2 emissions, such advances lead to the efficient use of the resources hence reduces the harm given to the environment. Cement process requires fine grinding of a material blend hence recent studies have been focusing on the improvements in these applications. The idea of dry stirred milling has come up with that aim and has been under investigation for many years. This study aims to show the possible applications of this technology within the cement grinding processes by discussing the quality and energy consumption aspects. In this context, sampling campaigns at a real plant were arranged initially and then simulation studies were undertaken by using the pilot scale test results obtained from a dry horizontal stirred mill. Basically, grinding of two different streams, classifier feed and coarse, were considered and necessary calculations had been performed. The results had proved that deploying the stirred media mill at these streams, provided energy saving between 7 and 18% and quality improvement by 2.8%. With its results shared, the paper is believed to contribute both the research and industry with its proposed flow sheet design for cement grinding circuits. The knowledge gained from this application can also be transferred to other applications requiring dry fine grinding.